2001
DOI: 10.1007/s002590100510
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between rest MIBG and exercise tetrofosmin defects: possible use of rest MIBG imaging as a marker of reversible ischaemia

Abstract: Perfusion imaging combined with pharmacological stress is the study of choice in patients with ischaemic heart disease who are incapable of exercising. Some medical conditions, however, can preclude the use of pharmacological stress. In these particular situations, availability of a diagnostic test which allows for the assessment of ischaemic territory at rest would be desirable. With the purpose of providing a marker of reversible ischaemia, we evaluated myocardial iodine-123 metaiodobenzylguanidine (MIBG) up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This concordance suggests that resting imaging with 123 ImIBG combined with resting myocardial perfusion imaging (MPI) may be useful as a marker of reversible ischemia in patients unable to exercise and with contraindications to pharmacological stress (27). Another potential role of mIBG imaging at rest is the detection of transient ischemia, which has been shown with metabolic tracers of both fatty acid and glucose analogs, termed "ischemic memory," that may result in regional decrease in mIBG uptake (28 -32).…”
Section: Imaging With 123 I-mibg In Ischemic Heart Diseasementioning
confidence: 81%
“…This concordance suggests that resting imaging with 123 ImIBG combined with resting myocardial perfusion imaging (MPI) may be useful as a marker of reversible ischemia in patients unable to exercise and with contraindications to pharmacological stress (27). Another potential role of mIBG imaging at rest is the detection of transient ischemia, which has been shown with metabolic tracers of both fatty acid and glucose analogs, termed "ischemic memory," that may result in regional decrease in mIBG uptake (28 -32).…”
Section: Imaging With 123 I-mibg In Ischemic Heart Diseasementioning
confidence: 81%
“…Estorch et al . reported that in patients who developed angina during exercise test, the area of denervated but perfused myocardium was significantly larger than in subjects without angina 23 . Matsunari and coworkers reported similar findings: Sympathetic neuronal damage measured by 123 I-mIBG was larger than the infarct size assessed by perfusion imaging, suggesting higher susceptibility of sympathetic neurons compared to cardiac myocytes 21 .…”
Section: Discussionmentioning
confidence: 94%
“…Although most of these studies relied primarily on planar imaging determinations of HMR and washout rate, some also included measurements from SPECT examinations because of the realization that SPECT may overcome the difficulties of planar imaging, including superposition of noncardiac structures and lack of segmental analysis (Fig. 1) 123 I-MIBG SPECT has been shown to be complementary to planar imaging in studies of coronary artery disease after an acute myocardial infarction (MI) (23,24). Viable but denervated myocardium has been shown to be supersensitive to the effects of infused catecholamines (25), which may provide a substrate for the genesis of ventricular arrhythmias.…”
Section: I-mibg Spect Complements Planar Imagingmentioning
confidence: 99%